Linked color imaging improves the diagnostic accuracy of eosinophilic esophagitis - Yasuhiko Abe; Yu Sasaki; Makoto Yagi; Naoko Mizumoto; Yusuke Onozato; Takashi Kon; Masakuni Shoji; Kazuhiro Sakuta; Takayuki Sakai; Matsuki Umehara; Minami Ito; Shuhei Nakamura; et al. (DEN Open)
Abstract Objectives To assess the usefulness of linked color imaging (LCI), a recently developed image‐enhanced endoscopy technique, in the endoscopic diagnosis of eosinophilic esophagitis (EoE). Methods Thirty white light images (WLIs) and 30 WLI+LCI images collected from patients with and without EoE were randomly and blindly reviewed by 10 endoscopists, including four experts (Exs) and six non‐Exs. Edema, ring, exudate furrows, and strictures were rated on the adjusted EoE endoscopic reference score; the diagnosis of EoE was assessed. Using the kappa value, inter‐ and intra‐observer agreements were analyzed among endoscopists. Results WLI+LCI images had a higher diagnostic accuracy for EoE than WLIs (0.85 vs. 0.70, respectively), especially in non‐Exs or endoscopists with no experience with EoE patients. Inter‐observer agreement for WLI+LCI images statistically surpassed WLIs for furrows (kappa, 0.73 vs. 0.67, respectively; p = 0.0013), stricture (kappa, 0.51 vs. 0.39, respectively; p = 0.0072), and diagnosis (kappa, 0.67 vs. 0.57, respectively; p < 0.0001) of EoE. The increase in inter‐observer agreement in WLI+LCI images allowed for a reduction in the differences between the Exs and non‐Ex endoscopists. Intra‐observer agreement for WLI+LCI images surpassed WLIs for a ring (kappa, 0.62 vs. 0.43, p = 0.0052), and a similar trend was found in exudates, furrows, and diagnosis irrespective of the Exs or non‐Exs. Conclusions LCI can contribute to the improvement of the endoscopic diagnosis for EoE, with “moderate” to “substantial” consistency, by enhancing the visibility of abnormal findings, leading to reduced diagnostic disparities among endoscopists.